Strategies for Optimizing Reporting and Recording Management to Improve Compliance in Philanthropic Organizations (LAZIS AL-HAROMAIN Case Study) - Engga Aji Pradana, Rivaldo; Choiruz Zen, Taufiq; Baldan Amin, Ajid; Ayu Firnanda, Aprilia (Program Studi Manajemen Zakat dan Wakaf, 2025)
In an effort to improve compliance in philanthropic institutions, especially in Lazis Al-Haromain, this research will examine the application of the reporting and recording management optimization approach. In maintaining accountability and transparency to stakeholders, including creditors, funders, and regulators, professionalism in financial management is essential. Efficient financial management not only ensures the smooth operation of the institution, but also increases public trust in the institution. To collect accurate and comprehensive data regarding financial recording and reporting procedures, this research utilizes qualitative methodology by conducting direct interviews with Lazis Al-Haromain’s financial management staff. Based on the results of the research, Lazis Al-Haromain has utilized the APEBESIT application and cloud-based systems to improve the effectiveness of financial recording and reporting. The research findings show that Lazis Al-Haromain improves the efficiency of financial recording and reporting by utilizing the APEBESIT application and cloud-based systems. Technology increases the accuracy of the data provided, reduces errors, and speeds up the financial administration process. Therefore, the use of technology in financial reporting and recording is essential to improve the professionalism and compliance of philanthropic institutions. Lazis Al-Haromain has also incorporated Standard Opening Procedures (SPOs) into the APEBESIT application to mitigate hazards that may occur. Following the internal SOPs that have been created by the institution to guarantee compliance with financial norms and regulations is how risk mitigation is implemented.